Notes on Cordyceps species Collected from the Central Region of Nepal - Shrestha, Bhushan (The Korean Society of Mycology, 2005)
The present study was carried out to explore the Cordyceps species and other entomopathogenic fungal flora around Kathmandu Valley and a few high altitude locations of Nepal. In this paper, we report eight Cordyceps species as new to Nepal: C. gracilis, C. ishikariensis, C. liangshanensis, C. martialis, C. militaris, C. pruinosa, C. sphecocephala and C. tricentri. We also mention a few allied genera such as Beauveria, Hirsutella and Paecilomyces from Nepal. Further collections from different ecological regions of Nepal will show the richness of entomopathogenic fungal floral diversity of Nepal.